Enterprise modelling in the context of manufacturing: Outline of an approach supporting production planning - Jonas Sprenger; Jürgen Jung (Universität Duisburg-Essen, Institut für Informatik und Wirtschaftsinformatik (ICB), 2008)
Manufacturing enterprises are faced with an increasing global competition and dynamic markets. This development results in a need for more flexible manufacturing structures and the ability for global collaboration. In the curse of this, cross-functional information systems turn into an essential competitive factor. However, the analysis and the integration of an enterprise's core functions is a major challenge. A model-centric approach, namely, multi-perspective enterprise modelling, is an appropriate conceptual instrument to overcome those gaps. Enterprise modelling is widely regarded as an appropriate tool to support analysing, designing and managing corporate information systems. In the paper at hand, we propose an approach fostering the applicability of enterprise models by offering domain-specific concepts. These modelling concepts reflect domain-specific concepts, which are well-known to manufacturing people. Hence, they are particularly suitable for supporting specific analyses, as well as information systems' development.
Keywords: 650; Verarbeitendes Gewerbe; PPS-System; Prozessmanagement; Integriertes Informationssystem